Analisis Pengaruh Kualitas Pelayanan, Harga Dan Promosi Digital Terhadap Kepuasan Konsumen Pada Bisnis Minuman Kekinian: Analysis Of The Effect Of Service Quality, Price And Digital Promotion On Consumer Satisfaction In The Modern Beverage Business - Umar, Abdul; Hestiana, Eka; Wahdaniyah; Sasti, Novia Tri; Paryanti, Atik Budi (OGZ Research & Publishing, 2026)
Abstract: The rapid expansion of trendy beverage businesses in Indonesia is closely linked to shifts in consumer lifestyles and the growing dominance of digital media. This development has intensified market competition, compelling business actors to focus not only on product innovation but also on service excellence, competitive pricing, and effective digital promotional activities. These elements are critical in shaping consumer perceptions and determining satisfaction levels. Nevertheless, many businesses in this sector have not managed these factors optimally, which can result in declining customer satisfaction and weakened loyalty. Objective : In response to this condition, this study investigates the effects of service quality, price, and digital promotion on consumer satisfaction within the trendy beverage industry. Methodology : The study used a quantitative approach with an explanatory design. Research results : The results are expected to identify key determinants of satisfaction and provide practical guidance for businesses in formulating more effective service and marketing strategies.